Characteristics of sedimentary environments in brackish marsh soils in relation to organic matter properties (Puck Lagoon, Northern Poland) - Hulisz, Piotr; Krześlak, Iwona; Karasiewicz, Mirosław T. (Ecological Questions, 2012)
The research focused on brackish marsh soils located within the coastal zone of Puck Lagoon (the Beka botanical and ornithological nature reserve). They are characterised by the presence of layers rich with allochthonous organic matter, derived from washing out of peat deposits. The objective of the research was to determine sedimentary environments of the soil organic matter based on selected properties. The obtained results indicated that despite similar morphological characteristics, these soils might have developed in slightly different environmental conditions, determined mostly by the Baltic water levels and morphology of the coast. The organic matter of the studied soils was characterised by relatively low aromaticity, which may indicate the ongoing process of decomposition. The presence of both peat-bog, rush and ruderal plants, as well as trees in the species composition of macroremains proved the heterogeneity of sedimentary environments and confirmed the allochthonous origin of organic matter accumulated in the studied brackish marsh soils.